Comunicação plurimidiática ou comunicação de massa? as metáforas coloniais na divulgação da Royal Academy of Dance (RAD) no Brasil - Costa, Leila Ortiz Tavares (2011)
The Royal Academy of Dance (RAD) produces multimedia material to disseminate itself all over the world. The Brazil gets a part where RAD is in action. This multimedia material puts together websites www.rad.co.uk, www.radacadabra.org, www.benesh.org, www.geneeballetcompetition.com, www.youngdances.org.uk end www.royalacademyofdance.com.br, CDs, DVDs, the Dance Gazette magazine (three edition in each year), Diary (four edition in each year), the syllabus of RAD (1991) and the books: The Foundation of Classical Ballet Technique (1997), Body Basic (1991) and Music in Dance Studio (1993) and some informative. It is purposing to study that complete multimedia material who the RAD uses to disseminate itself in the Brazil, this research make use of HP methodology hermeneutic of depth (THOMPSON, 2009) to analyse these different medias into the symbolic issues of production and reception from structural context. The aim is to demonstrate powerful potential contamination that RAD organized by your multimedia option giving emphasis in the other kind of media, not explicitly included in the multimedia material: the teacher of RAD. Proposing the teacher of RAD like a bodymedia (KATZ &GREINER, 2001, 2005, 2010) who disseminates the same information like the others medias giving effectiveness exponential for them into dissemination. Understanding the reception like a creative action, here is the reflection about teacher of RAD like a communication mechanism of power that gives potential to stabilize into students bodies asymmetric relation of power. The hypothesis is the teacher of RAD mediates specific knowledge (in the way of English to dance) that legitimizes structural of social class from neo-liberalism. How it despises the relation body-environment without getting the flow exchange of information who body is characterized (KATZ & GREINER), and getting communication model inputprocessing- output the teacher of RAD is like actuator of inputs that produces genuine in the way of English to dance without local construction potential of body (SANTOS, 2006). From this design, the research proposes coexistence between practical movement of both, teacher and student, guide by reflection that the teacher of RAD puts in motion colonial action when doesn t proposing exchange with environment (SANTOS, 2010; CANCLINI, 2007; HALL, 1997) and, in this action that operates the imposition to become yourself potential operator of biopolitcs